Professional Identity Formation in Medical Education for Humanistic, Resilient Physicians. (June 2015) - Wald, Hedy S.; Anthony, David; Hutchinson, Tom A.; Liben, Stephen; Smilovitch, Mark; Donato, Anthony A.
<x xml:space="preserve">Abstract</x> Recent calls for an expanded perspective on medical education and training include focusing on complexities of professional identity formation (PIF). Medical educators are challenged to facilitate the active constructive, integrative developmental process of PIF within standardized and personalized and/or formal and informal curricular approaches. How can we best support the complex iterative PIF process for a humanistic, resilient health care professional? How can we effectively scaffold the necessary critical reflective learning and practice skill set for our learners to support the shaping of a professional identity? The authors present three pedagogic innovations contributing to the PIF process within undergraduate and graduate medical education (GME) at their institutions. These are (1) interactive reflective writing fostering reflective capacity, emotional awareness, and resiliency (as complexities within physician–patient interactions are explored) for personal and professional development; (2) synergistic teaching modules about mindful clinical practice and resilient responses to difficult interactions, to foster clinician resilience and enhanced well-being for effective professional functioning; and (3) strategies for effective use of a professional development e-portfolio and faculty development of reflective coaching skills in GME. These strategies as "bridges from theory to practice" embody and integrate key elements of promoting and enriching PIF, including guided reflection, the significant role of relationships (faculty and peers), mindfulness, adequate feedback, and creating collaborative learning environments. Ideally, such pedagogic innovations can make a significant contribution toward enhancing quality of care and caring with resilience for the being, relating, and doing of a humanistic health care professional.